2021
DOI: 10.1111/jar.12948
|View full text |Cite
|
Sign up to set email alerts
|

Postural balance problems in people with intellectual disabilities: Do not forget the sensory input systems

Abstract: Background This pilot study aimed to explore the impact of visual, auditory and vestibular dysfunctions on the postural balance performance in adults with intellectual disabilities. Additionally, a comparison was made between the subjects with intellectual disabilities and a control group concerning static and dynamic balance tasks. Method Thirty adults with intellectual disabilities and 25 control subjects received a postural balance assessment. Additionally, the experimental group was subjected to a visual, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 61 publications
(107 reference statements)
0
17
0
Order By: Relevance
“…In line with our results, Granacher & Gollhofer (2011) did not find a significant correlation between static and dynamic strength with postural balance in a group of adolescents with IDs, while Blomqvist et al (2013) only reported several minor correlations between body mass index and strength with balance performance also in adolescents with IDs. These results highlight the necessity to consider certain peripheral sensory deficits often experienced by adults with IDs (Blomqvist et al 2013;Leyssens et al 2022).…”
Section: Discussionmentioning
confidence: 87%
“…In line with our results, Granacher & Gollhofer (2011) did not find a significant correlation between static and dynamic strength with postural balance in a group of adolescents with IDs, while Blomqvist et al (2013) only reported several minor correlations between body mass index and strength with balance performance also in adolescents with IDs. These results highlight the necessity to consider certain peripheral sensory deficits often experienced by adults with IDs (Blomqvist et al 2013;Leyssens et al 2022).…”
Section: Discussionmentioning
confidence: 87%
“…We cannot establish the possible cause of the better performance of the IH group in postural balance. Possible multisensory deficits in conditioning balance (Leyssens et al, 2022) could be compensated. This compensation is due to the heterogeneity of the sample in terms of the aetiology of intellectual disability.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the high‐precision of the automatic system used to collect force variables should also be considered, whereas three attempts were performed for the postural balance test and the median value was selected to increase the accuracy of the measurement. Considering the above mentioned methodological factors, and the fact that many previous studies comparing strength and/or balance variables between groups of people with different intellectual disabilities recruited similar sample sizes ( n from 20 to 55) (Delgado‐Lobete et al, 2021; Leyssens et al, 2022; Oppewal & Hilgenkamp, 2018), we believe that the findings of this study obtained through the application of a rigorous testing methodology significantly contribute to expand our knowledge regarding the differences in physical fitness between individuals with intellectual disabilities living in residential homes or independently. However, due to the small sample size, only the differences categorised as moderate or large (ES ≥ 0.50) reached statistical significance in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of exercise interventions on balance in individuals with intellectual disabilities remain inconclusive (Suárez-Iglesias et al, 2021). The underlying mechanisms contributing to balance impairment in this population are multifactorial and involve premature aging, obesity, physical inactivity, neurological disturbances, altered executive function, and peripheral sensory deficits (Leyssens et al, 2022). Thus, it is plausible that a multidisciplinary approach could be a more accurate strategy for achieving balance improvements in adults with intellectual disabilities (Kovačič et al, 2020).…”
Section: Discussionmentioning
confidence: 99%